Anxious attachment and belief in conspiracy theories. (15th April 2018) - Green, Ricky; Douglas, Karen M.
Abstract: This research examined the link between attachment styles and belief in conspiracy theories. It was hypothesized, due to the tendency to exaggerate the intensity of threats, that higher anxiously attached individuals would be more likely to hold conspiracy beliefs, even when accounting for other variables such as right-wing authoritarianism, interpersonal trust, and demographic factors that have been found to predict conspiracy belief in previous research. In Study 1 ( N  = 246 Amazon Mechanical Turk workers), participants higher in anxious attachment style showed a greater tendency to believe in conspiracy theories. Further, this relationship remained significant when accounting for other known predictors of conspiracy belief. Study 2 ( N =  230 Prolific Academic workers) revealed that anxious attachment again predicted the general tendency to believe conspiracy theories, but also belief in specific conspiracy theories and conspiracy theories about groups. These relationships held when controlling for demographic factors. The current studies add to the body of research investigating the individual differences predictors of conspiracy belief, demonstrating that conspiracy belief may, to some degree, have roots in early childhood experiences. Highlights: Two studies examined the relationship between attachment styles and conspiracy belief. Anxious attachment style predicted conspiracy belief. Avoidant and secure attachment styles did not predict conspiracy belief. Analyses controlled for other predictors of conspiracy belief (e.g., trust, demographics).